The Application of the Project Based Learning Model to Increase the Creativity of Class IV Students on Changes in Energy Forms at SDN Indrakila - Resmana, Lisna Permayanti; Iman, Bagus Nurul; Asyiah, Nur (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2024)
This research aims to evaluate the effectiveness of implementing the project based learning model in increasing the creativity of class IV students in the material on changing forms of energy at SDN Indrakila. In this research, data was collected through two methods, namely observation and questionnaires. The data analysis techniques applied in this research include qualitative and quantitative approaches. Qualitative data was obtained through observation, while quantitative data was obtained through learning outcomes tests. Based on the results of research conducted over two cycles, several conclusions can be drawn: (1) There is a significant increase in student creativity from Cycle I to Cycle II, with the “Good” category (81.25%) in Cycle I increasing to “Very Good” (above 90%) in Cycle II, indicating that the project based learning model is effective in increasing student creativity; (2) Student learning outcomes also experienced a significant increase, from the “Good” category (average score 3.71) in Cycle I to “Very High” (average score above 3.5) in Cycle II, showing an increase student understanding of the material; (3) Observations and feedback from teachers show that students are more involved and motivated, show enthusiasm, better teamwork, and initiative in exploring learning material.